Respon Pasar Terhadap Informasi Biaya Penelitian dan Pengembangan - Yessy Yuliana; Carmel Meiden (Owner : Riset dan Jurnal Akuntansi, 2022)
Value relevance shows how widely available accounting information can reflect the firm value. Accounting information is relevant if it can influence decision-making. In addition to information on earnings and book value, which are the basic variables in value relevance research, there is other accounting information that can explain the market value of the firms. In this study, other accounting information used is research and development cost and advertising cost that can provide benefits to the company in the future. This study aims to analyze and examine the effect of research and development costs and advertising costs on the market value of the firms. This study is using secondary data observation techniques acquired from annual financial reports for companies in the manufacturing industry sector that are listed on the Indonesia Stock Exchange in the 2011-2020 period. The sampling method used in this research is purposive sampling, with a total of 90 observations. The results of this study partially explain that research and development costs have a positive and significant effect on the market value of the firms, whereas advertising costs have a negative effect. Meanwhile, simultaneously the research and development costs and advertising costs with a control variables affect the market value of the firms. The conclusion of this study explains that research and development costs have a value relevance